Evaluation of the impact of air pollutants on university indoor air quality: a case study - Sabry Elattar, Sherif Mohamed; Abdullah, Ibrahim Dosoki; Abbas Saleh Gebriel, Amr (Frontiers in Built Environment, 2025)
This study evaluates indoor air quality in university lecture halls, focusing on the impact of interior finishes on air pollutant levels. Key pollutants monitored included Particulate Matter (PM2.5 and PM10), Carbon Dioxide (CO2), Sulphur Dioxide (SO2), Nitrogen Dioxide (NO2), formaldehyde (HCHO), and total volatile organic compounds (TVOCs), with sources identified as industrial emissions and traffic. Measurements were conducted in three distinct indoor environments at an Egyptian university during July 2024. Results showed that PM2.5 and PM10 concentrations remained within the World Health Organization (WHO) guidelines, whereas CO2 levels varied notably, with Lecture Hall 1 recording 713 ppm and Lecture Hall 2 reaching 1,071 ppm, indicating inadequate ventilation in the latter. Notably, NO2 and HCHO concentrations exceeded WHO recommended limits, with Lecture Hall 1 measuring 160 μg/m3 for NO2 and formaldehyde levels ranging between 430 μg/m3 and 1,380 μg/m3 across the halls. Based on these findings, we recommend that indoor air quality assessments follow the evaluation framework outlined in this study. Furthermore, we advocate for the enhancement of educational buildings through the implementation of design codes aimed at preserving and improving indoor air quality in lecture halls. Additionally, the study underscores the importance of raising awareness among students and faculty to foster healthier educational environments.